2009
DOI: 10.1177/1756287209104830
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic retroperitoneal lymph node dissection for stage I and II nonseminomatous germ-cell tumors

Abstract: Abstract:Objectives: Open retroperitoneal lymph node dissection has been traditionally used for the management of patients with nonseminomatous germ-cell tumors (NSGCTs). Over the last decade, laparoscopic retroperitoneal lymph node dissection (LRPLND) has gained popularity in several highly specialized centers. Methods: We retrospectively reviewed the English-language literature with regard to LRPLND. The perioperative and oncologic outcomes for patients with low stage NSGCTs who underwent LRPLND are summariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…A more recent study by Maldonado-Valadez et al [33] in 2007, reported no conversions in 17 patients and no intra- and postoperative complications. Nevertheless, L-RPLND after chemotherapy is a technically very demanding procedure, particularly in patients with SGCT and should only be attempted by surgeons with extensive laparoscopic experience [35] .…”
Section: Resultsmentioning
confidence: 99%
“…A more recent study by Maldonado-Valadez et al [33] in 2007, reported no conversions in 17 patients and no intra- and postoperative complications. Nevertheless, L-RPLND after chemotherapy is a technically very demanding procedure, particularly in patients with SGCT and should only be attempted by surgeons with extensive laparoscopic experience [35] .…”
Section: Resultsmentioning
confidence: 99%
“…Originally, Stephenson and Klein 13 reported that laparoscopic RPLND should be used only as a staging procedure and not as a therapeutic procedure. However, Guzzo and Allaf, 14 in their series, reported that laparoscopic RPLND can be accepted as a therapeutic option and not just used as a staging procedure. Albqami and Janetschek 4 demonstrated through an extensive quality of life study that patient satisfaction was higher with laparoscopic RPLND than with open RPLND.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure exhibits a faster recovery than traditional laparotomy as well as better oncological outcomes due to central ligation of the vessels and the extended lymphadectomy [2,3]. The challenge with laparoscopic CME is the exposure of the vessels at their roots, as there are many variations in the vascular anatomy of the right colon [4]. Here, we present an approach, a cranial plus medial-to-lateral method, to manage the vessels safely and effectively at their roots in laparoscopic right hemicolectomy with CME.…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…Laparoscopy has been proven to be as good as the traditional technique in cancer control rates [1,2], with the known advantages of a laparoscopic procedure for, for example, better pain control, reduction of morbidity and length of hospital stay [3,4].…”
mentioning
confidence: 99%